تدریس اورانتقالِ علم کا نظامیاتی مطالعہ قرآن و حدیث سے استدلال: A systematic study of Transferring and Explanation of knowledge Theoretical way of Qur’an and Hadith - Tariq, Faiza; Farooq, Dr. Saima (Al-Amīr Research Journal for Islamic Studies, 2024)
This article explores the special guidance in the Qur’an and Hadith towards the principles and manners of transferring and explanation of knowledge because of the greatness and status of it. It also finds that the system of these manners and principles encompasses with the strength of self-awareness and self-accountability. The systematic study of the transferring and explanation of knowledge is a clarification of the fact that the teaching, transferring, certification and chain of certificates for those who have mastered the arts in the present age are a part of Islamic traditions from the beginning. It concludes that the system of transferring and explanation, should not be a mere means of obtaining degrees, but should have a good quality of understanding, ease and influence in the human being. Therefore, the entire education system of Muslims has strong and good Islamic foundations. Key Words: Qur’an, Hadith, Knowledge, Seeking Knowledge, Transfer of Knowledge.